2006
DOI: 10.1093/toxsci/kfl151
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Onset of Aberrant Gene Expression Relevant to Pulmonary Carcinogenesis in Lung Adenocarcinoma Development Induced by In Utero Arsenic Exposure

Abstract: Arsenic is a human pulmonary carcinogen. Our work indicates that in utero arsenic exposure in mice can induce or initiate lung cancer in female offspring. To define early molecular changes, pregnant C3H mice were given 85 ppm arsenic in drinking water from days 8 to 18 of gestation and expression of selected genes in the fetal lung or in lung tumors developing in adults was examined. Transplacental arsenic exposure increased estrogen receptor-alpha (ER-alpha) transcript and protein levels in the female fetal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 44 publications
4
51
0
1
Order By: Relevance
“…The expression of HSD17β5 dehydrogenase, an enzyme catalyzing the transformation of 4-androstenedione (4-dione) into testosterone, was also decreased. These changes are consistent with male liver feminization and a role of aberrant estrogen signaling seen in our series of transplacental arsenic carcinogenesis studies (Waalkes et al, 2004b(Waalkes et al, , 2006aLiu et al, 2006Shen et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The expression of HSD17β5 dehydrogenase, an enzyme catalyzing the transformation of 4-androstenedione (4-dione) into testosterone, was also decreased. These changes are consistent with male liver feminization and a role of aberrant estrogen signaling seen in our series of transplacental arsenic carcinogenesis studies (Waalkes et al, 2004b(Waalkes et al, , 2006aLiu et al, 2006Shen et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…We found that those who started drinking well water from birth, still drank at enrollment, and drank it for long period were at a significantly increased risk of urinary cancer, especially urothelial carcinoma. Evidence from experimental studies (19)(20)(21)(22) showed that early-life exposure to arsenic may increase the health risks during early childhood and later in life. Up to date, only one ecologic study (23) conducted in Chile showed that exposure to arsenic in drinking water during early childhood or in utero was associated with an increased mortality in young adults from both malignant and nonmalignant lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental impact of arsenic also includes dysfunction of endocrine (Tseng et al, 2000) and reproductive systems (Singh & Rana, 2007). Limited evidence suggests that adverse human reproductive effects of arsenic may include higher risk of low birth weight, spontaneous abortion, preeclampsia, congenital malformation, infant mortality (Ahmad et al, 2001) and carcinoma incidence to the new born (Shen et al, 2007). In experimental rodent model, arsenic has been reported to produce toxic effects on female reproductive system (Chattopadhyay et al, 1999).…”
Section: Introductionmentioning
confidence: 99%